Pengaruh Etika Kepemimpinan, Kompetensi Sumber Daya Manusia dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan - Ni Wayan Anggun Eka Lestari; Sang Ayu Putu Arie Indraswarawati (UNHI Press, 2022)
This research was conducted at LPD Se-Subdistrict Gianyar which uses technology in recording financial statements with a population of 34 LPD in Gianyar Subdistrict with 215 employees. The study sample used a purposive sampling method with a sample number 150 respondents. The analysis technique used is multiple linear regression analysis with data collection methods using questionnaires The results of the research on leadership ethics have a positive and significant effect on the quality of reports with sig 0.000 <0.05. Human resource competence has a positive and significant effect on the quality of reports with sig 0.004 <0.05. The use of information technology has a positive and significant effect on the quality of reports with a significance of 0.000 <0.05.